Enhance non-homogeneous Poisson process models incorporating testing effort with coverage function. Issue 3 (4th May 2017) - Shinde, Vikas; Kumar, Jitendra
Abstract: In this paper, we studied the software reliability models for evaluating the reliability growth of a product. We discussed improve enhance NHPP model which differs from previously reported NHPP based models it explain categorically the time changing test coverage function. Which provide its analytical formulation and defect detection during the testing and operational mode. Parameters estimation have been carried out to estimate the various foil rate with test coverage function